Предмет: Алгебра,
автор: Аноним
Упрости выражение: (13+3√3)⋅(13−3√3)
Ответы
Автор ответа:
0
Ответ:
v - знак корня.
(13+3v3)(13-3v3) = 13²-(3v3)² = 169-9×3 = 169-27 = 142.
Автор ответа:
0
Используем формулу сокращенного умножения
(а-в) (а+в) = а²-в²
(13+3√3)⋅(13−3√3) = 13² - (3√3)² = 169 - 9*3 = 169 - 27 = 142
Ответ: 142.
Похожие вопросы
Предмет: Обществознание,
автор: karinina14
Предмет: Английский язык,
автор: satella77
Предмет: Математика,
автор: itaev
Предмет: Математика,
автор: Диана090980
Предмет: Математика,
автор: vikasiz